2000
DOI: 10.1016/s0014-5793(00)01550-7
|View full text |Cite
|
Sign up to set email alerts
|

Sequence, genomic structure and tissue expression of carp (Cyprinus carpio L.) vertebrate ancient (VA) opsin

Abstract: We report the isolation and characterisation of a novel opsin cDNA from the retina and pineal of the common carp (Cyprinus carpio L.). When a comparison of the amino acid sequences of salmon vertebrate ancient opsin (sVA) and the novel carp opsin are made, and the carboxyl terminus is omitted, the level of identity between these two opsins is 81% and represents the second example of the VA opsin family. We have therefore termed this C. carpio opsin as carp VA opsin (cVA opsin). We show that members of the VA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…The usual splicing mechanism consists in exon shuffling and several regulatory peptides, including calcitonin gene-related peptide, gastrin-releasing peptide, and the pro-opiomelanocortin family, are produced in this fashion (Sausville et al 1986, Garrett et al 1989, Lou & Gagel 1998. Intron retention is not the most common mechanism for alternative splicing, but many references can be found in the literature describing this process (Lupetti et al 1998, Unsworth et al 1999, Moutsaki et al 2000, Weiss et al 2000. In the AM gene, the retention of the third intron creates a truncated preprohormone because it introduces a premature in-frame termination codon.…”
Section: Discussionmentioning
confidence: 99%
“…The usual splicing mechanism consists in exon shuffling and several regulatory peptides, including calcitonin gene-related peptide, gastrin-releasing peptide, and the pro-opiomelanocortin family, are produced in this fashion (Sausville et al 1986, Garrett et al 1989, Lou & Gagel 1998. Intron retention is not the most common mechanism for alternative splicing, but many references can be found in the literature describing this process (Lupetti et al 1998, Unsworth et al 1999, Moutsaki et al 2000, Weiss et al 2000. In the AM gene, the retention of the third intron creates a truncated preprohormone because it introduces a premature in-frame termination codon.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering work by Foster and Soni in 1997 first suggested that fish use blue light to encode irradiance information: Since then, members of a previously uncharacterised vertebrate ancient (VA) opsin family with maximum sensitivities at wavelengths between 460 and 500 nm have been identified in the eyes of Atlantic salmon (Philp et al 2000;Soni and Foster 1997;Soni et al 1998), carp (Moutsaki et al 2000), zebrafish (Kojima et al 2000) and smelt (Minamoto and Shimizu 2002). In addition, melanopsin genes have been identified in zebrafish (Bellingham et al 2002) and Atlantic cod (Drivenes et al 2003).…”
Section: Predictionsmentioning
confidence: 99%
“…Similarly, the use of molecular biological methods have contributed to the identification of several 'new' types of opsins and other putative photopigments in the pineal complex, like parapinopsin (Blackshaw & Snyder 1997a), vertebrate ancient opsins (Soni et al 1998;Moutsaki et al 2000), exo-rhodopsin (Mano et al 1999), extra-retinal rod-like opsin (Philp et al 2000a) and cryptochromes (Kobayashi et al 2000). Unfortunately, the in situ hybridization labelling patterns have not so far been correlated with morphologically identified pineal photoreceptor types.…”
Section: Are There Really Many Types Of Pineal Photoreceptors?mentioning
confidence: 99%